Content Analysis on the Origins of Islamic Economics: Contextualized Interpretation of Two Bibliographies in the 20th Century - Orhan, Zeyneb Hafsa (Intellectual Discourse, 2018)
Since its formal inception in the early 20th century, Islamic economics has been considered a modern phenomenon, even though its foundations can be traced back to the earliest of Muslim civilizations. However, despite Islamic economics being more than half a century old, there are many serious issues, such as epistemological and methodological concerns, that need to be resolved. In order to delve into such matters, a clear understanding of the origins of modern Islamic economics is necessary. Hence, some of the important questions are: who are its initiators, what were they especially interested in, and how have its subject matter, agenda and intentions changed through different time-periods. Accordingly, the aim of this paper is to focus on and evaluate the course of the early development of Islamic economics via two bibliographies of Siddiqi (1975), and Zaim (1980). In order to attain this aim, content analysis using excel-generated heat maps are used to facilitate contextualized interpretation. More specifically, heat maps for the two selected works mentioned above are created from the two bibliographies in order to make comparisons between them.